Impaired Pancreatic β-Cell Function in Critically Ill Children - Shereen A. Mohamed; Nora E. Badawi; Hoiyda A. AbdelRasol; Hossam M. AbdelAziz; Nirvana A. Khalaf; Remon M. Yousef (Frontiers Media S.A., 2021)
Critical illness hyperglycemia (CIH) is common in the pediatric intensive care unit (PICU). Increased glucose production, insulin resistance (IR), and pancreatic β-cell dysfunction are responsible mechanisms. We aimed to investigate β-cell function in the PICU and to uncover its relation to clinical and laboratory variables and ICU mortality. We prospectively recruited 91 children. Pancreatic β-cell function was assessed by using a homeostasis model assessment (HOMA)-β. Patients with β-cell function <40.0% had significantly higher Pediatric Risk of Mortality III (PRISM III) scores, higher rates of a positive C-reactive protein (CRP), lower IR, and a longer hospital stay. The patients with 40-80% β-cell function had the highest IR. Intermediate IR was found when the β-cell function was >80%. ICU survivors had better β-cell function than ICU non-survivors. A multivariate logistic regression analysis revealed that higher PRISM III score and HOMA-β <80.0% were significant predictors of mortality. In conclusion, β-cell dysfunction is prevalent among PICU patients and influences patient morbidity and mortality.